2019
DOI: 10.3390/en12050806
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigations on the Fluidized Heat Absorption inside Quartz Glass and Metal Tubes

Abstract: Air as a heat transfer fluid has been widely studied in concentrated solar-power generations, but the solar energy absorbed by air inside transparent and opaque tubes has not been comparatively investigated. The heat transfer was studied experimentally and numerically for a fluidized granular bed air receiver with a non-uniform energy flux and the fluidization occurs inside cylindrical metal and quartz glass tubes. The experiments were conducted in a solar simulator with 19 xenon short-arc lamps and showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…FBs have been employed for solar energy applications, considering configurations operating in bubbling, spouted, circulating regimes (see Table 1, Types A-C "ordinary" configurations), and special and novel designs (Types D-J). Early studies successfully pioneered the application of ordinary FBs operated in the bubbling (Flamant, 1982;Bachovchin et al, 1983) and circulating (Koenigsdorff and Kienzle, 1991;Werther et al, 1994) inherent mobility of fluidized particles received further confirmation in subsequent studies (Flamant et al, 1988;Glicksman et al, 1988;Chirone et al, 2013;Pardo et al, 2014;Schwaiger et al, 2014;Salatino et al, 2016;Tregambi et al, 2016;Milanese et al, 2017a;Tregambi et al, 2018a;Briongos et al, 2018;Miller et al, 2018;Bellan et al, 2019a;Tregambi et al, 2019a;Almendros-Ibáñez et al, 2019;Zhang and Wang, 2019;Sulzgruber et al, 2020a;Díaz-Heras et al, 2020b;Sulzgruber et al, 2020b;Park et al, 2020;Wünsch et al, 2020). Moreover, FBs, if properly designed and operated, may provide an appropriate environment for solar-driven heterogeneous chemical processes.…”
Section: Fluidized Bed Solar Receivers and Reactors: Basic Design And Operational Features Particle Receivers And Fluidized Bedsmentioning
confidence: 99%
“…FBs have been employed for solar energy applications, considering configurations operating in bubbling, spouted, circulating regimes (see Table 1, Types A-C "ordinary" configurations), and special and novel designs (Types D-J). Early studies successfully pioneered the application of ordinary FBs operated in the bubbling (Flamant, 1982;Bachovchin et al, 1983) and circulating (Koenigsdorff and Kienzle, 1991;Werther et al, 1994) inherent mobility of fluidized particles received further confirmation in subsequent studies (Flamant et al, 1988;Glicksman et al, 1988;Chirone et al, 2013;Pardo et al, 2014;Schwaiger et al, 2014;Salatino et al, 2016;Tregambi et al, 2016;Milanese et al, 2017a;Tregambi et al, 2018a;Briongos et al, 2018;Miller et al, 2018;Bellan et al, 2019a;Tregambi et al, 2019a;Almendros-Ibáñez et al, 2019;Zhang and Wang, 2019;Sulzgruber et al, 2020a;Díaz-Heras et al, 2020b;Sulzgruber et al, 2020b;Park et al, 2020;Wünsch et al, 2020). Moreover, FBs, if properly designed and operated, may provide an appropriate environment for solar-driven heterogeneous chemical processes.…”
Section: Fluidized Bed Solar Receivers and Reactors: Basic Design And Operational Features Particle Receivers And Fluidized Bedsmentioning
confidence: 99%
“…Doherty et al [8] conducted experiments to investigate the heat transfer coefficient of a horizontal smooth tube immersed in a gas-liquid bed and the results showed that the heat transfer coefficient of the gas and liquid phase decreases at first as the outer diameter of tube is increased but increases as the diameter is further increased. Zhang and Wang [9] studied the heat transfer for a fluidized granular bed air receiver experimentally and numerically with a non-uniform energy flux and the fluidization occurs inside cylindrical metal and quartz glass tubes and a numerical model was established to study the fluidized heat transport inside the quartz tube. Cong et al [10] obtained the total heat transfer coefficient through logarithmic mean temperature difference method and conducted an experimental study on the heat transfer of a gas-solid two-phase mixture.…”
Section: Introductionmentioning
confidence: 99%